METHODOLOGICAL BACKGROUND AND FOUNDATIONS OF THE NONMATERIAL THEORY OF THE PSYCHE - Reshetnikov , M. M. (Modern Psychology, 2019)
The problem of the psyche and consciousness has been the most mysterious one for a few thousand years and is still unresolved. It has been almost forgotten that Aristotle considered human psyche a structure that is not bound to the body. This idea did not persist, though. It was Hippocrates who ruined it and declared a different concept, which prevailed for many centuries, that the brain is a repository of all mental processes. Even such a genius as Rene Descartes took Hippocrates’s idea for granted and spent many months in attempts to find memory and emotions in gyrus and ventricles of the brain. This path – the search of material structures of the psyche – was followed by I.M. Sechenov, I.P.Pavlov and many others. Later, many other mistaken ideas were born, declared new and revolutionary ones and died prematurely. However, not only ideas died, but also patients, who were treated by methods developed on the basis of these hypotheses. The author formulates the idea of the brain as the biological interface and proves a non-material theory of the psyche, which is a discovery that requires a change in basic paradigms of human sciences.